Representations of *-algebras, locally compact groups, and Banach *-algebraic bundles. - Fell, J. M. G. (James Michael Gardner), 1923- (Pure and applied mathematics (Academic Press), 1988)
This is an all-encompassing and exhaustive exposition of the theory of infinite-dimensional Unitary Representations of Locally Compact Groups and its generalization to representations of Banach algebras. The presentation is detailed, accessible, and self-contained (except for some elementary knowledge in algebra, topology, and abstract measure theory). In the later chapters the reader is brought to the frontiers of present-day knowledge in the area of Mackey normal subgroup analysisand its generalization to the context of Banach *-Algebraic Bundles.